(untitled) (Acta Scientiarum. Biological Sciences, 2012)
Disruption of protein digestion in insects by specific endoprotease inhibitors is being regarded as an alternative to conventional insecticides for pest control. To optimize the effectiveness of this strategy, the understanding of the endoprotease diversity of the target insect is crucial. In this sense, a membrane-bound trypsin-like enzyme from the gut of Anticarsia gemmatalis fifth-instar larvae was purified. Non-soluble fraction of the gut extract was solubilized with 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate (CHAPS) and subjected to a p-aminobenzamidine affinity chromatography followed by anion-exchange chromatography. The yield of the purified enzyme was 11% with a purification factor of 143 and a final specific activity of 18.6 µM min.-1 mg-1 protein using N-Î±-benzoyl-L- Arg-p-nitroanilide (L-BApNA) as substrate. The purified sample showed a single band with proteolytic activity active and apparent molecular mass of 25 kDa on SDS-PAGE. Molecular mass determined by MALDI-TOF mass spectrometry was 28,632 ± 26 Da. Although the low recovery and the difficulties in purifying large enzyme amounts limited its further characterization, the results contribute for the understanding of the proteases present on A. gemmatalis gut, which are potential targets for natural or specifically designed protease inhibitors.